(untitled) (Perner’s Contacts, 2019)
The article focuses on the problem of the lack of professional drivers. Information from the European Job Mobility Portal (EURES) and statistical data from the Czech Labor Offices, the Integrated portal of the Ministry of Labor and Social Affairs, the Czech Statistical Office, the Transport Yearbook 2017 and other sources are summarized in the article. The factors that cause the lack of professional drivers in the labor market are mentioned as well. The article presents specific options for solution of this problem. There is presented an example of education of a new driver by utilizing of the European Social Fund (ESF) project for educational activities - Support of Vocational Training for Employees (POVEZ II) in more detail way.